Computational simulations for the hepatic arterial buffer response after liver graft transplantation from an adult to a child. (January 2020) - Yu, H.B.; Bartlett, A.; Hunter, P.; Ho, H.
Highlights: A first numerical simulation for hepatic flow in a liver graft in a paediatric recipient has been made. Simulation results show that HABR may play a role in hepatic flow regulation in recipients. HABR may be associated with thrombosis formation in portal-hyperperfusion and venous occlusion. Abstract: Live donor liver transplantation (LDLT) is an important surgical technique for treating children with end-stage liver diseases. Surgical complications may occur, e.g., due to thrombosis formed in hepatic arteries (HAs) or portal veins (PVs). From the hepatic circulation point of view, a hepatic arterial buffer response (HABR) mechanism, where the HA flow counteracts the changes in the PV flow, could play a role in graft dysfunction, yet this intricate mechanism has not been elucidated in LDLT procedures. In this short communication we simulate the HABR which may occur in an adult-to-child LDLT, where the left lateral lobe of an adult donor is transplanted to a child. Using an electrical analog model we show that the HABR could be triggered in both portal hyper-perfusion and venous obstruction scenarios, and this may be associated with arterial and/or venous thrombosis in the liver graft as reported in clinical studies. In conclusion, HABR could be important in adult-to-child LDLT and it should be considered in pre-surgical planning.